Pengaruh Kompetensi SDM, Kualitas Informasi Keuangan dan Locus Of Control Terhadap Kinerja UMKM dengan Pengambilan Keputusan Sebagai Variabel Intervening - Rudi Suryo Kristanto; Yohana Kus Suparwati; Suci Atiningsih; Asri Nur Wahyuni (JIEF : Journal of Islamic Economics and Finance, 2021)
This study aims to determine the effect of human resource competence, quality of financial information, and locus of control on the performance of MSMEs with decision making as an intervening variable at Lurik UMKM Centers in Pedan District and Batik Centers in Bayat District, Klaten Regency. The population in this study were the Lurik UMKM centers in Pedan District and the Bayat Batik Centers, which are the assistance of the Klaten Regency Cooperative and UMKM Service. The sampling technique used random sampling. Methods of data analysis using path analysis. The results of this study are: human resource competence and quality of financial information have an effect on decision making. Locus of control has no effect on decision making. HR competency has no effect on the performance of MSMEs. The quality of financial information and locus of control affect the performance of MSMEs and decision making affects the performance of MSMEs.